P128 Inside Out Health Project: how do male prisoners experience HIV healthcare in English prisons? An exploration of patient's experiences and opinions. (16th June 2022) - Young, Felicity
Abstract : Introduction: 'People living with HIV should be at the centre of their own care, with the ability to have meaningful involvement in the development and delivery of services' (BHVA, 2018). However, there is little evidence in the literature of the experiences of people living with HIV in prison, and none which relates to their involvement with English prison healthcare service. People living with HIV have a chronic health concern, experience stigma, and have increased social disadvantage. Those in prison are more frequently from marginalised and disadvantaged social groups and who experience poorer health outcomes. Living with HIV, whilst incarcerated, may further diminish health-related outcomes and quality of life. Methods: People living with HIV who are in prison have a particular and special experience but appear to be unrepresented in decisions related to HIV healthcare. This qualitative study, planned with a research patient and public involvement (PPI) group, will undertake one-to-one interviews to gather data about those experiences. Data will be analysed using reflexive thematic analysis. Results: The research findings will inform draft recommendations for best practice. Participants and those in the PPI group will be invited to participate in a Delphi-style review of the draft recommendation to co-produce the final output. Discussion: Managing HIV effectively during detention must be a priority for providers, commissioners, and those with responsibility for healthcare provision in the criminal justice system. In conjunction with participants this project aims to better understand the issues and to make recommendations for best practice to contribute to high-quality HIV care in prison. References: BHIVA (2018) British HIV Association standards of care for people living with HIV 2013. London: British HIV Association. Braun V and Clarke V (2006) Using thematic analysis in psychology. Qualitative Research in Psychology; 3 (2): 77-101 Turan B, Hatcher A M, Weiser S D, Johnson M O, Rice W S and Turan J M (2017) Framing mechanisms linking HIV-related stigma, adherence to treatment and health outcomes. American Journal of Public Health; 107 (6): 863-869 Rich J D, Beckwith C G, Macmadu A, Marshall, Brandon D L, Brinkley-Rubinstein L, Amon J J, Milloy M-J, King M R F, Sanchez J, Atwoli L and Altice F L (2016) Clinical care of incarcerated people with HIV, viral hepatitis, or tuberculosis. The Lancet; (388) 10049: 1103-1114 Singer M, Bulled N, Ostrach B, Mendenhall E. Syndemics and the biosocial conception of health (2017) The Lancet; (389) 10072: 941-950